Constructing the patriarchal city : gender and the built environments of London, Dublin, Toronto, and Chicago, 1870s into the 1940s - Flanagan, Maureen A., 1948- (Urban life, landscape, and policy., 2018)
"In the Anglo-Atlantic world of the late nineteenth century, groups of urban residents struggled to reconstruct their cities in the wake of industrialization and to create the modern city. New professional men wanted an orderly city that functioned for economic development. Women's vision challenged the men's right to reconstruct the city and resisted the prevailing male idea that women in public caused the city's disorder. Constructing the Patriarchal City compares the ideas and activities of men and women in four English-speaking cities that shared similar ideological, professional, and political contexts. Historian Maureen Flanagan investigates how ideas about gender shaped the patriarchal city as men used their expertise in architecture, engineering, and planning to fashion a built environment for male economic enterprise and to confine women in the private home. Women consistently challenged men to produce a more equitable social infrastructure that included housing that would keep people inside the city, public toilets for women as well as men, housing for single, working women, and public spaces that were open and safe for all residents"--